Revitalizing Soil Phosphorus Fertility: The Transformative Potential - Dipak Ranjan Biswas (Journal of the Indian Society of Soil Science, 2026)
It is indeed a great privilege to deliver the 41st Professor J.N. Mukherjee - ISSS Foundation lecture during the Global Soils Conference 2024 - Caring Soils Beyond Food Security: Climate Change Mitigation & Ecosystem Services, organized by the Indian Society of Soil Science (ISSS), New Delhi, India under the aegis of International Union of Soil Sciences (IUSS), in collaboration with Indian Council of Agricultural Research (ICAR), New Delhi and National Academy of Agricultural Sciences (NAAS), New Delhi. I am most thankful to the ISSS for inviting and giving me the opportunity to deliver the prestigious Prof. J.N. Mukherjee-ISSS Foundation Lecture. I feel honoured to join the eminent scientists who delivered the foundation lecture in the past. I pay my humble homage and tribute to Prof. Jnanendra Nath Mukherjee who was an outstanding scientist, teacher par excellence, able administrator and a great visionary. He was also the Founder Secretary of the ISSS, established on 22nd December 1934 in Calcutta (now Kolkata) with 28 members, in the Physical Chemistry Laboratory, Presidency College, University of Calcutta, with Sir B.C. Burt, the then Agricultural Commissioner of the Imperial (now Indian) Council of Agricultural Research as the First President. Prof. Mukherjee was a student of Presidency College (1909- 1915) and received his B.Sc. (1913) and M.Sc. (1915) degrees from the Calcutta University. Based on his thesis for M.Sc. Degree, a paper on Electric Synthesis of Colloids was published in the Journal of the American Chemical Society (1915). In 1919, Prof. Mukherjee joined the University College, London to work in the Physical Chemistry Laboratory under Prof. F.G. Donnan, FRS. Prof. Mukherjee continued his research on colloids and his major line of work was to develop the theory of the electrokinetic double layer and its ionic constitution. Prof. Mukherjee, recipient of Doctor of Science in 1921 from University of London, had specialization in electrochemistry, colloids, and soil science. His work on the electrochemistry of colloids is considered highly significant. He is also well known for the boundary method he developed for determining the cataphoretic speed of colloid particles. He was a man of colloid science, the very base of soil science.